Improving Vocational Ability To Grow Hydroponics Through Direct Learning Models For Children With Light Mental Retardation - Esi Efriza; Zulmiyetri Zulmiyetri (EDUCATIO : Journal of Education, 2019)
The background of the problem in this study is to look at the vocational ability to grow hydroponics for light mental retardation children in Perwari Padang Slb. The problem is found that children have not been able to do hydroponic farming because hydroponic farming has never been taught to children. The purpose of this study was to prove whether the direct learning model can improve the ability to grow hydroponics for light mental retardation children in class VIII C in Perwari Padang SLB. This type of research is an experimental research that is by using quasi-experimental or also called quasi-experiment with a single group design of pretest and posttest. Based on the results of the study This study concludes that the direct learning model can improve the vocational skills of hydroponic cultivation for light mental retardation children in class VIII C in Perwari Padang SLB. The results of this study can be taken into consideration for teachers to be able to use direct learning models to improve children's vocational abilities, especially in teaching how to grow crops in a hydroponic manner.